Beyond respiration: Controls on lateral carbon fluxes across the terrestrial‐aquatic interface. Issue 3 (19th February 2018) - Tank, Suzanne E.; Fellman, Jason B.; Hood, Eran; Kritzberg, Emma S.
Abstract: Understanding what controls the lateral flux of organic and inorganic carbon from landscapes to surface waters is key to fully understanding terrestrial ecosystem carbon balances, the biogeochemistry of freshwaters, and how the hydrologically‐mediated movement of carbon between these ecosystems may be altered by global change. In this paper, we synthesize current knowledge and identify major knowledge gaps in our understanding of land‐to‐water fluxes of dissolved and particulate organic carbon, CO2, and bicarbonate by exploring: (1) how variations in soil carbon stocks affect dissolved and gaseous carbon production in the soil profile and transport via terrestrial‐aquatic flow paths, and (2) the effect of global change on these lateral carbon fluxes. Our aim is to develop a roadmap to guide future research on terrestrial‐aquatic linkages in the carbon cycle within the context of changes in climate, global biogeochemical cycles, and land use.